A co-produced national climate change risk and vulnerability assessment framework for South Africa - Ziervogel, Gina; Taylor, Anna (Frontiers in Climate, 2023)
There are mounting demands to undertake climate risk and vulnerability (CRV) assessments for policy, planning, funding, insurance and compliance reasons. In Africa, given the adaptation imperative, this is particularly important. Increasingly, it has become clear that sub-national assessments are needed to inform adaptation practice. However, there has been relatively little guidance on how to undertake these more local assessments and aggregate them making it difficult for national governments to know the extent and variability of climate vulnerability and risk across the country. In South Africa, the national government, led by the Department of Forestry, Fisheries and the Environment (DFFE), undertook to establish a common framework to guide the development and review of CRV assessments. This paper presents the framework that was co-developed through a series of engagements with stakeholders active in implementing and supporting CRV assessments. The framework is intended to provide guidance on what to consider when undertaking CRV assessments within diverse South African contexts in order to enable alignment, comparison and aggregation between them and work towards an effective climate adaptation response across scales. Rather than standardising a methodology, the framework promotes the use of a standard set of concepts as the basis for each assessment and profiles a diversity of methods, tools and data sources for applying the concepts in a contextually sensitive way. This provides a flexible yet structured sequence of three interlinked steps in a risk and vulnerability assessment process, namely: 1) Planning, 2) Scoping and 3) Assessing. The framework guides users through the choice and application of three assessment depths, depending on decision-context, resourcing and extent of preexisting data and information. It encourages the integration of participatory and indicator-based methods through an impact chain approach, profiling more than thirty freely available tools and resources. This process builds a strong evidence base and a deepening set of engagements and shared understanding between relevant stakeholders, upon which to act. This South African process can provide insight and support for actors driving the climate agenda in other countries looking to develop comparable assessments as the basis to drive equitable and transformative climate action and learning.